Distillery Spentwash Irrigation on the Nutrients of Banana (Musa paraisica) and Papaya (Carcia papaya) Fruits - C. S. Chidankumar2, S. Chandraju1* and (Journal of Phytology, 2010)
SUMMARY Cultivation of Banana (Musa paradisiaca) and Papaya (Carcia papaya) plants was made by irrigation with distillery spentwash of different proportions. The distillery spentwash i.e., primary treated spentwash (PTSW), 50%, 33% and 20% distillery spentwash were analyzed for plant nutrients such as nitrogen, phosphorous, potassium(NPK) and other physical and chemical parameters. The plants were cultivated by irrigation with raw water (RW), 50%, 33% and 20% distillery spentwash in the prepared land. The impact of distillery spentwash on proximate principles (moisture, protein, fat, fibre, carbohydrate, energy, calcium, phosphorous, and iron), Vitamin content (carotene and vitamin-c), mineral and trace elements (magnesium, sodium, potassium, copper, manganese, zinc, chromium and nickel) i.e., nutritive value of ripened fruits were analyzed. It was observed that good nutrients uptake in fruits in the case of 20% spentwash than compared with 33%, 50% spentwash and raw water irrigations. This could be due to the maximum absorption of NPK by plants at more diluted condition of spentwash. This concludes that the diluted spentwash can be conveniently used for the effective cultivation without using any external fertilizers. Hence, spentwash serves as a liquid fertilizer, eco-friendly irrigation medium and without adverse effect on environment and soil. Key words: Distillery spentwash, Fruits, Nutrients, Proximate principles, Minerals <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">S. Chandraju1 and C. S. Chidankumar. Distillery Spentwash Irrigation on the Nutrients of Banana (Musa paraisica) and Papaya (Carcia papaya) Fruits. J Phytol 2/6 (2010) 28-33